1997
DOI: 10.1038/sj.cdd.4400267
|View full text |Cite
|
Sign up to set email alerts
|

Lack of ‘tissue’ transglutaminase protein cross-linking leads to leakage of macromolecules from dying cells: relationship to development of autoimmunity in MRLlpr/lpr mice

Abstract: Genetic defects of the CD95 (Fas/Apo-1) receptor/ligand system, has recently been involved in the development of human and murine autoimmunity. We investigated whether a deregulation of the`tissue' transglutaminase (tTG), a multifunctional enzyme which is part of the molecular program of apoptosis, may act as a cofactor in the development of autoimmunity. We found that MRLlpr/lpr, which are characterized by a defect in the CD95 receptor and suffer of a severe systemic lupus erythematosus-like disease, produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
65
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 33 publications
1
65
0
Order By: Relevance
“…Inhibition of TGase expression (with antisense expression vectors) results in a reciprocal decrease in apoptotic activity (Melino et al, 1994). It is thought that the formation of a densely cross-linked intracellular matrix contributes to the fragmentation of cells during apoptosis as well as preventing the leakage of intracellular proteins during the formation of apoptotic bodies (Piredda et al, 1997).…”
mentioning
confidence: 99%
“…Inhibition of TGase expression (with antisense expression vectors) results in a reciprocal decrease in apoptotic activity (Melino et al, 1994). It is thought that the formation of a densely cross-linked intracellular matrix contributes to the fragmentation of cells during apoptosis as well as preventing the leakage of intracellular proteins during the formation of apoptotic bodies (Piredda et al, 1997).…”
mentioning
confidence: 99%
“…Here we present data suggesting the involvement of this receptor in the CD pathogenesis. Interestingly, a deregulated tTG is present in autoimmunity-prone MRL lpr/lpr mice, 13 where tTG is also detected into the ECM similarly to the wound healing process and tissue repair occurring in CD lesions. Several studies have indicated that tTG, by crosslinking a number of proteins such as collagens, fibronectin, laminin, nidogen and Transforming Growth Factor-1, might play an important role in the modification of the ECM occurring in degenerative diseases.…”
Section: Dear Editormentioning
confidence: 99%
“…8 As evidenced by the presence of high levels of e(g-glutamyl)lysine crosslinks mucosae from CD patients were biopsied, fixed and stained with anti-tTG (1-2, 7) anti-CD95L (5,6), or anti-e(g-glutamyl)lysine crosslinks (8) antibodies as well as by TUNEL for DNA fragmentation (3,4) as previously described. 10,12,13 Compared to controls (7) in early stages of the disease (1, 3, 5) tTG staining is detected in the enterocytes localised in the upper part of the villi and in the fibroblasts lining the intestinal epithelium (arrows; 1), while DNA fragmentation (3) and a strong CD95L staining (5) were confined to the enterocytes. In the cute stage of the disease (2,4,6,8), characterized by villus flattening, a large proportion of the tTG staining was detected in the extracellular matrix of the lesion and only a limited number of fibroblasts were stained (2).…”
Section: Dear Editormentioning
confidence: 99%
“…7,8 Recently, Piredda et al reported that an inactive form of tissue transglutaminase accumulates in lymphoid organs of MRL lpr/lpr mice, which are characterized by a lymphoproliferative autoimmune disorder strongly resembling human Systemic Lupus Erythematosus (SLE). 6,9 These mice carry a mutated inactive form of the CD95-Fas antigen, a protein that plays a key role in apoptosis; nonetheless, this defect can only partially explain the pathogenesis of the lpr phenotype and other components must play a role in conferring genetic susceptibility. 9 We tested whether polymorphisms or mutations in the tissue transglutaminase (Tgm2) gene account for the observed accumulation and/or the reduced activity of this enzyme in lymphoid organs of lpr mice.…”
Section: Dear Editormentioning
confidence: 99%
“…This may prevent inflammatory responses as well as provide dissequestration of self antigens which could lead to the development of autoimmunity. 6 Notably, a major role for tissue' transglutaminase has been proposed in the insurgence of autoimmune Celiac Disease as well as in some neurodegenerative disorders characterized by polyglutamine expansions. 7,8 Recently, Piredda et al reported that an inactive form of tissue transglutaminase accumulates in lymphoid organs of MRL lpr/lpr mice, which are characterized by a lymphoproliferative autoimmune disorder strongly resembling human Systemic Lupus Erythematosus (SLE).…”
Section: Dear Editormentioning
confidence: 99%